A Rare Case of Urachal Carcinoma Metastatic to Thoracic Vertebra Detected by FDG PET/CT. (July 2017) - Yang, Guangjie; Wang, Zhenguang; Liu, Simin; Wu, Fengyu; Li, Dacheng
Abstract : Abstract: Both chest radiography and MRI scan showed compression fracture of the T6 vertebral body in a 33-year-old man who presented with back pain. Because of the absence of predisposing factors for compression fracture, a pathologic fracture was considered. For this reason, an FDG PET/CT was performed. The images revealed not only the abnormal activity in the known T6 vertebral body but also an additional activity immediately anterosuperior to the urinary bladder in a partially calcified soft tissue nodule. A mucinous adenocarcinoma of urachus with solitary bone metastasis was confirmed histopathologically.